2017
DOI: 10.1007/s11356-017-8867-y
|View full text |Cite
|
Sign up to set email alerts
|

Microbial degradation of chloroethenes: a review

Abstract: Contamination by chloroethenes has a severe negative effect on both the environment and human health. This has prompted intensive remediation activity in recent years, along with research into the efficacy of natural microbial communities for degrading toxic chloroethenes into less harmful compounds. Microbial degradation of chloroethenes can take place either through anaerobic organohalide respiration, where chloroethenes serve as electron acceptors; anaerobic and aerobic metabolic degradation, where chloroet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 266 publications
1
85
0
Order By: Relevance
“…In situ bioremediation is a cost-effective and environmentally-friendly approach to reach eco-toxicological safety endpoints at chlorinated ethene-contaminated sites (Stroo et al 2010). Among all reported dehalogenating microorganisms (Maymo-Gatell et al 1997, Holliger et al 1998, Löffler et al 2000, Adrian et al 2000, Suyama et al 2001, Sung et al 2006, Hug et al 2013, Dolinova et al 2017, Dehalococcoides mccartyi is the only known species that metabolically reductively dechlorinates PCE and TCE to non-toxic ethene. Many studies on D. mccartyi-containing microbial communities have been carried out in the past decades (Carr et al 2000, Cupples et al 2004, Freeborn et al 2005, Yu et al 2005, Daprato et al 2007, Duhamel et al 2007, Ziv-El et al 2012, with the identification of optimal growth conditions supporting D. mccartyi and functional robustness determinants of dechlorinating activity.…”
Section: Introductionmentioning
confidence: 99%
“…In situ bioremediation is a cost-effective and environmentally-friendly approach to reach eco-toxicological safety endpoints at chlorinated ethene-contaminated sites (Stroo et al 2010). Among all reported dehalogenating microorganisms (Maymo-Gatell et al 1997, Holliger et al 1998, Löffler et al 2000, Adrian et al 2000, Suyama et al 2001, Sung et al 2006, Hug et al 2013, Dolinova et al 2017, Dehalococcoides mccartyi is the only known species that metabolically reductively dechlorinates PCE and TCE to non-toxic ethene. Many studies on D. mccartyi-containing microbial communities have been carried out in the past decades (Carr et al 2000, Cupples et al 2004, Freeborn et al 2005, Yu et al 2005, Daprato et al 2007, Duhamel et al 2007, Ziv-El et al 2012, with the identification of optimal growth conditions supporting D. mccartyi and functional robustness determinants of dechlorinating activity.…”
Section: Introductionmentioning
confidence: 99%
“…Both of them involve degradation through monooxygenase-catalysed epoxidation [25], with the initial step catalysed by cytochrome P450 monooxygenase. Epoxides can be degraded subsequently either by epoxyalkane, coenzyme M transferase or through formation of glutathione conjugates [26,27].Only a few studies have focused on parallel presence of anaerobic dechlorinators and aerobic methanotrophs or ethenotrophs at contaminated sites. Liang et al [20] studied the potential for VC degradation at six contaminated sites based on abundance and expression of VC biodegradation genes, and suggested that both ethenotrophs and anaerobic VC dechlorinators simultaneously contributed to VC biodegradation at the sites with high VC attenuation rates.…”
mentioning
confidence: 99%
“…Both of them involve degradation through monooxygenase-catalysed epoxidation [25], with the initial step catalysed by cytochrome P450 monooxygenase. Epoxides can be degraded subsequently either by epoxyalkane, coenzyme M transferase or through formation of glutathione conjugates [26,27].…”
mentioning
confidence: 99%
“…Although nZVI toxicity to microorganisms has been demonstrated in laboratory studies [12][13][14], field studies show only mild or short-term impacts on indigenous bacterial populations [15][16][17]. OHRB include a range of bacterial genera, including Desulfitobacterium, Dehalobacter, Geobacter and Sulfurospirillum, all of which utilize different reductases that can dechlorinate PCE to TCE and cis-1,2-dichloroethene (cDCE) [18]. However, only Dehalococcoides and Dehalogenimonas spp.…”
mentioning
confidence: 99%
“…In addition to anaerobic reductive dechlorination, degradation of CEs can also occur under aerobic conditions, either metabolically, where CEs are used as electron donors for cell growth, or by co-metabolism, where CEs are degraded fortuitously during the metabolism of other growth substrates, without gaining carbon or energy for bacterial growth [18]. Aerobic cometabolic degradation has been shown for all CEs, though only rarely described for PCE [22], and is related to certain aerobic bacteria, such as ethene oxidizers (ethenotrophs) and methane oxidizers (methanotrophs) [23][24][25].…”
mentioning
confidence: 99%